Slogans políticos em campanhas eleitorais no Rio Grande do Norte: a mídia na disputa ideológica. - Capistrano, Janaina Tomaz (2007)
To the observe the periods of electoral campaigns, we can realize sharply the abundance of political propaganda that announces the candidates, their campaign record, their proposed and everything that can carry them to the victory in the urns. The propaganda is today an essential tool in the votes dispute, in consequence of this, there is, in Brazil, the increasing participation of the Politics Parties in seminars of electoral marketing. They are varied strategies of the media used in the divulging of the candidacies, among them the slogan. Instigated by the explicit relation media/political, this work intends to investigate the ideologies (values) announced by the slogans of political propaganda that circulated in electoral periods. Thus, we base on the theory of the Circle of Bakhtin, who considers the statement as unit of the verbal communication, and that conceives the language as phenomenon dialogical, and, too, in the conceptions of alien words, social voices and dialogical relations formulated by the referred theory. We use, for better to comprehend, the slogan as strategy mediatic, of the classical study done by Olivier Reboul concerning the slogan; and, like starting point of a conception about ideology, studied John Thompson to comprehends the ideological phenomenon. Our corpus it constitutes of 14 political slogans announced in the campaigns for mayor of the cities in Natal and Mossoró, both located in Rio Grande do Norte s state, Brazil, in 1996, 2000 and 2004. For the analysis of these slogans, we consider the social-historical context in which were announced, being contemplated the linguistic and discursive aspect, according to the following methodological order: the identification of alien words (interdiscours); the social voices and the kinds dialogical relations established; and, finally, the ideology announced by the statement. This way, we can arrive to the conclusion that in the electoral context occurs a true ideologies war , in other words, in the political game of an electoral campaign, the slogans announces different values, which vary in several factors function, for example, the historicity, the subject that enunciates, the discursive positionings.